A biomechanical analysis of world-class senior and junior race walkers - Hanley, B. (New Studies in Athletics, 2013)
The purpose of this study was to conduct a biomechanical analysis of all 15 medallists at the 25th IAAF World Race Walking Cup in Saransk, Russia. Each of the medallists was videoed during the faster second half of the race. Two cameras were placed alongside the course and 3D analysis of the video data conducted in order to measure the most important variables in race walking. As expected, stride length correlated with velocity, and data on individual athletes emphasised the importance of this variable. However, longer strides were negatively associated with stride frequency, and so a balance between these two fundamental variables is advisable. The athletes adhered very closely to the race walking rule with regard to having a straightened knee at first contact; however, they were closer to the threshold of visibly losing contact. While there was little variation between athletes in terms of hip and knee angles, there were larger variations found within the measurements of shoulder and elbow angles. Coaches and athletes should be mindful that race walking is a whole-body activity and inefficient movements should be identified and corrected as appropriate.